Penerapan Project Penguatan Profil Pelajar Pancasila (P5) Pada Mata Pelajaran IPS Terpadu Siswa SMA Negeri 2 Percut Sei Tuan Untuk Meningkatkan Keberagaman Budaya Sebagai Aset Perekonomian Bangsa - Josua Adrio Sihombing; Karina Zahra; Malvira Pohan; Sernanda Putri Darma; Andi Taufiq Umar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This type of research is qualitative research with a case study model. This research aims to investigate the implementation of the P5 Program (Pancasila Student Profile Strengthening Project) in integrated social studies subjects at SMAN 2 Percut Sei Tuan with a focus on increasing students' understanding of cultural diversity as an asset for the nation's economy. The Strengthening Pancasila Student Profile Project aims to increase students' awareness of Pancasila values ​​and citizenship, as well as increasing students' ability to interact with various cultures in Indonesia. The method used is a qualitative method with a descriptive approach. Data was collected through observation, interviews and documentation at SMAN 2 Percut Sei Tuan, Medan. The research results show that cultural diversity in the school has a positive impact on student learning. The Strengthening Pancasila Student Profile Project succeeded in creating an inclusive learning atmosphere and respecting differences. Students showed a positive response to this program, which helped increase their understanding of cultural diversity and Pancasila values. The integration of cultural diversity in integrated social studies learning also makes a significant contribution to students' understanding of economic aspects. Through cultural diversity, students can understand the relationship between culture and economics, as well as the impact of globalization on these two aspects. In addition, practical activities such as the culinary bazaar are concrete evidence of the results of the P5 program, which helps promote the values ​​of cultural diversity, mutual respect, and build social inclusion among students. In conclusion, cultural diversity at SMAN 2 Percut Sei Tuan can be utilized optimally through the P5 Program to form students who are ready to face challenges in a diverse society.